Leisure in times of pandemic: The use of free time by adolescents in a municipality in the interior of the Amazon - Galvão, Edna Ferreira Coelho; Galvão, Juarez Bezerra; Galvão, Nalanda Coelho; Carvalho, Fernando Nascimento; Santana, Nicolas Máximo Andrade (Seven Editora, 2023)
This study sought to understand the main effects of social isolation during the COVID-19 pandemic on the use of free time by adolescents in a municipality in the interior of the Amazon. Participated in the research 70 adolescents, captured through digital platforms and indication of other adolescents who were accepting to participate in the study. The project was approved by the CEP of UEPA campus of Santarém. The data were collected through a form with closed and open questions produced in google forms and sent by Whatzapp to the participants. They only had access to the form after signing the ICF and Term of Assent. The data were analyzed with the support of Excel and Iramuteq software. The general results of the profile indicated that most of the participants were female (64.28%), with ages distributed between 11 and 19 years, the majority coming from public schools (58.57%), and the vast majority (90%) are residents of the urban area of the municipality, and (45.71%) live with up to two minimum wages. DOI:https://doi.org/10.56238/emerrelcovid19-029